Association between genetic risk of alcohol consumption and alcohol‐related morbidity and mortality under different alcohol policy conditions: Evidence from the Finnish alcohol price reduction of 2004. (13th January 2023) - Lahtinen, Hannu; Moustgaard, Heta; Ripatti, Samuli; Martikainen, Pekka
Abstract: Aims: Harmful alcohol consumption is influenced by both genetic susceptibility and the price of alcohol. Many previous studies have observed that genetic susceptibility to consumption of alcohol is more predictive in less restrictive drinking conditions. We assess whether such a pattern applies when the prices of alcoholic beverages are decreased. Design: Data consist of genetically informed population‐representative surveys (FINRISK 1992, 1997, 2002 and Health 2000) linked to administrative registers. We analysed the interaction between a polygenic score (PGS) for alcoholic drinks per week consumed and price reduction in predicting the incidence of alcohol‐related hospitalizations and deaths in difference‐in‐difference and interrupted time‐series frameworks. Setting: Individuals in Finland were followed quarter‐yearly from 1 March 2000 to 31 May 2008. Participants: A total of 22 152 individuals (607 132‐person quarter‐years, 1399 outcome events) aged 30–79 years. Intervention: A natural experiment stemming from the alcohol tax reduction in March 2004 and import deregulation in May 2004. Measurements: Outcome was quarter‐yearly‐measured alcohol‐related death or hospitalization. The independent variables of main interest were PGS and a price reform indicator. We adjusted for gender, age, age squared, season, 10 first principal components of the genome, data collection round and genotyping batch. Findings: Both alcohol price reduction and one standard deviation change in PGS were associated with alcohol‐related health outcomes; odds ratios (ORs) were 1.32, 95% confidence interval (CI) = 1.13, 1.53 and 1.26, 95% CI = 1.12, 1.42 in the 8‐year follow‐up, respectively. The association between PGS and alcohol‐related morbidity was similar before and after the alcohol price reform (PGS × price reform interaction OR = 0.96, 95% CI = 0.81, 1.14). These results were robust across different follow‐up periods and measurement and analysis strategies. Conclusions: Although the decrease of alcohol price in Finland in 2004 substantially increased overall alcohol‐related morbidity and mortality, the genetic susceptibility to alcohol consumption did not become more manifest in predicting them.